A "Total Slope Analysis" methodology applied to an unstable rock slope in Washington, USA (Journal of Nepal Geological Society, 2006)
A "Total Slope Analysis" methodology, that combines several numerical techniques, is adopted to investigate an unstable rock slope in Washington State, USA. For this specific study, the distinct-element code UDEC is used to assess the stability and potential failure volume of the rockslide. Once the potential rockslide volume has been estimated and failure mechanism assessed, the runout path, distance and velocity are assessed using the dynamic or rheological flow model DAN3D. Site investigation and data reconnaissance plays an important role for both stages in the "Total Slope Analysis", including outcrop mapping, aerial photograph interpretation, scanline joint surveys and 3-D laser scanning.The results of the "Total Slope Analysis" can be directly applied to assessment and mitigation of the landslide hazard, greatly aiding engineering judgment by providing key qualitative and quantitative insights into the risk analysis.